PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE EOQ DAN MRP PADA CV. OZONE GRAPHICS DI MANOKWARI - Millenia, Fitriani Tasya; Sudarwadi, Dirarini; Nurlaela, Nurlaela (Politeknik Negeri Ambon, 2022)
This study aims to analyze the amount of banner raw material inventory in 2020, with the selected method, namely EOQ and MRP to get an economical amount of inventory on the next order.This study uses primary data from interviews and secondary data from inventory report data from CV. Ozone Graphics. The analysis used is Economic Order Quantity (EOQ) and Material Requirement Planning (MRP) with the Part Period Balancing (PPB) technique.The results of this study using the EOQ method the company will get an optimal inventory of 422.94 meters of Korean Flexy and 42.58 liters of Icontek ink, with the lowest total inventory cost of Rp. 3,571,694.39 Korean Flexy and Icontek ink of Rp. IDR 3,496,425.47. Meanwhile, with the MRP method, the results obtained are that the total cost of inventory is too high, namely Korean Flexy Rp 12,930,250 and Rp 17,034,520 Icontek ink. So that by using the EOQ method the company will get the optimal amount of inventory and can minimize inventory costs.Keywords: Inventory, Inventory Cost, EOQ, MRP, PPB